2017
DOI: 10.1111/tri.13084
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of acute rejection after kidney transplantation

Abstract: SUMMARY Treatment of acute rejection (AR) following kidney transplantation has improved in recent years, but there are still limitations to successful outcomes. This review article covers literature in regard to recipient and donor genetics of AR kidney and secondarily of liver allografts. Many candidate gene and some genome-wide association studies (GWASs) have been conducted for AR in kidney transplantation. Genetic associations with AR in kidney and liver are mostly weak, and in most cases, the associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 151 publications
(101 reference statements)
1
27
0
1
Order By: Relevance
“…Acute renal allograft rejection (AR) is the single most important risk factor for developing chronic renal allograft rejection [4,5]. Numerous genetic polymorphisms have been determined to be associated with AR, including those in human leukocyte antigens (HLA) [6]. Despite the advances made in immunosuppression and technical care of renal transplant recipients, leading to an improvement in the first-year allograft survival, chronic renal allograft rejection continues to be a major impediment over the decades [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Acute renal allograft rejection (AR) is the single most important risk factor for developing chronic renal allograft rejection [4,5]. Numerous genetic polymorphisms have been determined to be associated with AR, including those in human leukocyte antigens (HLA) [6]. Despite the advances made in immunosuppression and technical care of renal transplant recipients, leading to an improvement in the first-year allograft survival, chronic renal allograft rejection continues to be a major impediment over the decades [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In this study we identified discrepancies in the current histological recognition of stable allografts and demonstrated a new Instability Score (or InstaScore), a linear combination of selected features based on the input from tissue gene expression and inferred cell type biopsy molecular data modeled on AR biology, that provides precise (sub-)phenotyping and early recognition of molecular and cellular rejection of otherwise functionally and histologically stable allografts on protocol biopsies. Unlike other published studies by others [61][62][63][64][65] and our group [2,54,66,67] that have only studied gene expression transcriptional perturbation in AR, this is the first development and application of a combined genes and cell types into Instability Score in tissue that can rapidly reclassify samples into molecularly and even more importantly, functionally relevant, diverse groups: those most similar to the normal kidneys (hSTA/mSTA) and those most similar to the rejected kidneys (hSTA/mAR).…”
Section: Discussionmentioning
confidence: 90%
“…Genetic association studies for transplant outcomes tend to look at the recipient genome only (Dorr, Oetting, Jacobson, & Israni, 2018). Individual recipient single nucleotide polymorphisms (SNPs) have been found to be associated with acute rejection outcomes for kidney, liver, and heart transplants (Almoguera et al, 2014; Green et al, 2017; Morris et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Individual recipient single nucleotide polymorphisms (SNPs) have been found to be associated with acute rejection outcomes for kidney, liver, and heart transplants (Almoguera et al, 2014; Green et al, 2017; Morris et al, 2015). Recipient's genes have also been found to affect pharmacogenetic outcomes, such as immunosuppressant concentration in transplant recipients (Almoguera et al, 2014; Dorr et al, 2018; Oetting et al, 2016). Multiple studies have examined how differences in transplant outcomes that seem to be based on self‐reported race may be because of underlying genetic differences between different ethnic groups (Green et al, 2017; Morris et al, 2015).…”
Section: Introductionmentioning
confidence: 99%